Historical Policy of Local Communities: Formal-Legal and Informal Foundations - Martynov, Mikhail Yurievich (Frontiers in Law, 2025)
The article examines the historical policy of institutionalized and non-institutionalized actors as tools for the formation of national identity and interethnic tolerance. Local communities, whose commemorative practices are family memory, as well as discourses on social networks, are considered as non-institutionalized factors. The research area is Khanty-Mansiysk Autonomous Area - Yugra. The methods used are content analysis of regulatory documents, as well as in-depth interviewing. Institutionalized and non-institutionalized means of historical policy are considered. It is concluded that historical policy implemented by local communities in the sphere of formation of interethnic tolerance has normative and legal support and is systematic. The differences between the narratives of historical policy at the local level and the official state discourse are noted. Informal practices of forming collective ideas about the past are not only trusted at the cognitive level, but also have a much deeper impact on the emotional sphere of people, appealing to images of family or local history. And this often turns out to be a factor that has a deeper impact on the formation of collective ideas about the past. As a result, in some cases the narratives of state historical policy are simply ignored by collective memory, while in others they can acquire a significantly different semantic content. Even in cases where collective ideas about the past seem to coincide with the official narrative, the concepts they operate with can have a significantly different semantic content compared to the indoctrinal position. As a result of this kind of aberration of historical memory, the connotations of historical events acquire completely different meanings in people’s memory compared to the official discourse.